Meanings of old age to the elderly in pondok living arrangement in Malaysia - Areff, Nor Aisah; Lyndon, Novel (MCSER-CEMAS-Sapienza University of Rome, 2015)
Previous studies have focussed on the meaning of old age as conducted from the quantitative approach. Thus the primary emphasis of this article is the perception of elderly individuals who resided in Pondok Jeram, an alternative congregated living arrangement which was established for the propagation of Islamic teaching and learning on old age. The employment of abductive research strategy based on idealist ontology and social constructionist epistemology gave the perennial importance to the elderly's point of views. The use of in-depth interviews yielded social actors' meaning and interpretation of old age in their everyday experience. The findings revealed 7 important themes in relation to understanding old age; old age as a natural life cycle, old age is normal, feeling about old age, old age and physical changes, old age and religion, old age and health and old age and pondok. Finally, the interpretations of elderly residents' meaning of old age would give a clearer understanding of their needs from the local socio-cultural environment for future policy planning and implementation concerning them. © 2015, Mediterranean Center of Social and Educational Research.